Drying and wetting of Mediterranean soils stimulates decomposition and carbon dioxide emission: the “Birch effect” - Jarvis, Paul; Rey, Ana; Petsikos, Charalampos; Wingate, Lisa; Rayment, Mark; Pereira, João; Banza, João; David, Jorge; Miglietta, Franco; Borghetti, Marco; Manca, Giovanni; Valentini, Riccardo (Tree Physiology, 2007)
Observations on the net carbon exchange of forests in the European Mediterranean region, measured recently by the eddy covariance method, have revived interest in a phenomenon first characterized on agricultural and forest soils in East Africa in the 1950s and 1960s by H. F. Birch and now often referred to as the “Birch effect.” When soils become dry during summer because of lack of rain, as is common in regions with Mediterranean climate, or are dried in the laboratory in controlled conditions, and are then rewetted by precipitation or irrigation, there is a burst of decomposition, mineralization and release of inorganic nitrogen and CO2. In forests in Mediterranean climates in southern Europe, this effect has been observed with eddy covariance techniques and soil respiration chambers at the stand and small plot scales, respectively. Following the early work of Birch, laboratory incubations of soils at controlled temperatures and water contents have been used to characterize CO2 release following the rewetting of dry soils. A simple empirical model based on laboratory incubations demonstrates that the amount of carbon mineralized over one year can be predicted from soil temperature and precipitation regime, provided that carbon lost as CO2 is taken into account. We show that the amount of carbon returned to the atmosphere following soil rewetting can reduce significantly the annual net carbon gain by Mediterranean forests.
10.1093/treephys/27.7.92910.1093/treephys/27.7.929
Keywords: carbon balance; carbon mineralization rates; Mediterranean climate; mediterranean forest; rain pulse; soil rewetting; Soil temperature; soil water; summer rainfall events

Drying and wetting of Mediterranean soils stimulates decomposition and carbon dioxide emission: the “Birch effect” - Jarvis, Paul; Rey, Ana; Petsikos, Charalampos; Wingate, Lisa; Rayment, Mark; Pereira, João; Banza, João; David, Jorge; Miglietta, Franco; Borghetti, Marco; Manca, Giovanni; Valentini, Riccardo (Tree Physiology, 2007)
Observations on the net carbon exchange of forests in the European Mediterranean region, measured recently by the eddy covariance method, have revived interest in a phenomenon first characterized on agricultural and forest soils in East Africa in the 1950s and 1960s by H. F. Birch and now often referred to as the “Birch effect.” When soils become dry during summer because of lack of rain, as is common in regions with Mediterranean climate, or are dried in the laboratory in controlled conditions, and are then rewetted by precipitation or irrigation, there is a burst of decomposition, mineralization and release of inorganic nitrogen and CO2. In forests in Mediterranean climates in southern Europe, this effect has been observed with eddy covariance techniques and soil respiration chambers at the stand and small plot scales, respectively. Following the early work of Birch, laboratory incubations of soils at controlled temperatures and water contents have been used to characterize CO2 release following the rewetting of dry soils. A simple empirical model based on laboratory incubations demonstrates that the amount of carbon mineralized over one year can be predicted from soil temperature and precipitation regime, provided that carbon lost as CO2 is taken into account. We show that the amount of carbon returned to the atmosphere following soil rewetting can reduce significantly the annual net carbon gain by Mediterranean forests.
10.1093/treephys/27.7.929
Keywords: carbon balance; carbon mineralization rates; Mediterranean climate; mediterranean forest; rain pulse; soil rewetting; Soil temperature; soil water; summer rainfall events

Variation in cold hardiness and carbohydrate concentration from dormancy induction to bud burst among provenances of three European oak species - Morin, Xavier; Améglio, Thierry; Ahas, Rein; Kurz-Besson, Cathy; Lanta, Vojtěch; Lebourgeois, François; Miglietta, Franco; Chuine, Isabelle (Tree Physiology, 2007)
Although cold hardiness is known to be a major determinant of tree species distribution, its dynamics and the factors that regulate it remain poorly understood. Variation in cold hardiness and carbohydrate concentration, from dormancy induction until bud burst, were investigated in populations of two deciduous (Quercus robur L. and Quercus pubescens Willd.) and one evergreen (Quercus ilex L.) European oak. Mean cold hardiness values in January were –56, –45 and –27 °C for Q. robur, Q. pubescens and Q. ilex, respectively. Soluble carbohydrate concentrations were closely related to instantaneous cold hardiness, estimated by the electrolyte leakage method, whereas total carbohydrate concentration was related to maximum cold hardiness. Both cold hardiness and carbohydrate concentration showed a close linear relationship with temperatures at the location of the sampled population. Our results show that temporal variation in both the inter- and intraspecific cold hardiness in European oaks can be related to variations in the concentrations of soluble carbohydrates and that these relationships appear to be driven by temperature.
10.1093/treephys/27.6.817
Keywords: adult individuals; climate; distribution; frost dam- age; natural populations; Phenology; Quercus ilex; Quercus pubescens; Quercus robur

Variation in cold hardiness and carbohydrate concentration from dormancy induction to bud burst among provenances of three European oak species - Morin, Xavier; Améglio, Thierry; Ahas, Rein; Kurz-Besson, Cathy; Lanta, Vojtěch; Lebourgeois, François; Miglietta, Franco; Chuine, Isabelle (Tree Physiology, 2007)
Although cold hardiness is known to be a major determinant of tree species distribution, its dynamics and the factors that regulate it remain poorly understood. Variation in cold hardiness and carbohydrate concentration, from dormancy induction until bud burst, were investigated in populations of two deciduous (Quercus robur L. and Quercus pubescens Willd.) and one evergreen (Quercus ilex L.) European oak. Mean cold hardiness values in January were –56, –45 and –27 °C for Q. robur, Q. pubescens and Q. ilex, respectively. Soluble carbohydrate concentrations were closely related to instantaneous cold hardiness, estimated by the electrolyte leakage method, whereas total carbohydrate concentration was related to maximum cold hardiness. Both cold hardiness and carbohydrate concentration showed a close linear relationship with temperatures at the location of the sampled population. Our results show that temporal variation in both the inter- and intraspecific cold hardiness in European oaks can be related to variations in the concentrations of soluble carbohydrates and that these relationships appear to be driven by temperature.
10.1093/treephys/27.6.81710.1093/treephys/27.6.817
Keywords: adult individuals; climate; distribution; frost dam- age; natural populations; Phenology; Quercus ilex; Quercus pubescens; Quercus robur

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 - Hättenschwiler, S; Miglietta, Franco; Raschi, Antonio; Körner, C (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.
Keywords: allometric adjustments; biomass allocation; branch morphology; branching; leaf area; Mediterranean; natural co 2 springs; Quercus ilex

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 - Hättenschwiler, S.; Miglietta, Franco; Raschi, Antonio; Körner, C. (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.
Keywords: allometric adjustments; biomass allocation; branch morphology; branching; leaf area; Mediterranean; natural co 2 springs; Quercus ilex